Effectiveness of Mindfulness Therapy on Mental Pain, Distress Tolerance, and Psychological Hardiness in Patients with Breast Cancer - Amiri, Majid; Salehi, Mina; Fattahi, Nabi; Sadeghzadeh, Rozita (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Cancer is the third leading cause of death in Iran following cardiovascular diseases, accidents, and other phenomena. The current research aimed to determine the effectiveness of mindfulness therapy on mental pain, distress tolerance, and psychological hardiness in patients with breast cancer.Methods and Materials: The present study employed a quasi-experimental design with pre-test, post-test, and a one-month follow-up, along with a control group. The population consisted of all female patients who visited clinics in the city of Babol in 2022 and were diagnosed with breast cancer. Out of this population, 30 patients with breast cancer were selected through non-random convenience sampling and randomly assigned into two groups: an experimental group (mindfulness therapy) and a control group (15 individuals in each group). Mindfulness therapy was then administered in 8 sessions of 90 minutes each for the experimental group. Data were collected using the Psychological Hardiness Questionnaire by Lang and Goulet (2003), the Distress Tolerance Scale by Simons and Gaher (2005), and the Mental Pain Questionnaire by Orbach and Mikulincer (2003). Data were analyzed using repeated measures ANOVA with SPSS software version 22.Findings: The results demonstrated that mindfulness therapy effectively reduced mental pain (P < 0.001), increased distress tolerance (P < 0.001), and enhanced psychological hardiness (P < 0.001) in patients with breast cancer.Conclusion: It can be concluded that mindfulness therapy was effective in reducing mental pain, increasing distress tolerance, and enhancing psychological hardiness in patients with breast cancer, and can be utilized to mitigate the adverse effects of the disease on patients' lives and for supportive interventions.